The contribution of physical exercise in the aging process - Ferreira, Kaio Bernardes; Freitas, André Hostalácio; Leal, José Carlos; Martins, Ivani Pose (Seven Editora, 2024)
This study aimed to analyze, through an integrative review, the benefits arising from regular physical exercise as an important component to alleviate functional changes resulting from aging. The research was carried out between October and November 2023, in the following databases: Medical Literature Search and Analysis Online System (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and BDENF (Base of Nursing Data), due to the credibility, variety and ease of finding articles in Portuguese and available in full for online access, using the Health Sciences Descriptors (DeCS): “physical exercise”, “aging” and “health of the elderly”, crossing with the Boolean operator AND. From the results found, it was evident that the practice of physical exercise is a healthy alternative to alleviate functional changes resulting from aging. DOI:https://doi.org/10.56238/sevened2023.007-056